Pregnancy in a Woman With Untreated Vesico-Cloacal Extrophy: A Clinical Case - Roch M’betid-Degana; Gilles-Davy Kossa-Ko-Ouakoua; Jonathan Sabah; Geniva Gracelia Vanciane M’betid-Degana; Hilary Mattie Kossa Yamenda; Antoine Doui-Doumgba (European Scientific Journal, ESJ, 2026)
Introduction: Pregnancy in patients with vesicocloacal exstrophy is extremely rare and poorly documented in the literature. Report case: We report the case of a 16-year-old adolescent with multiple congenital malformations who was pregnant, referred from a rural health facility without a technical platform and qualified human resources (Batangafo District Hospital) to a facility with limited resources (Sino-Central African Friendship University Hospital Center in Bangui, the capital of the Central African Republic). The patient was successfully surgically managed: a caesarean section was performed, resulting in the cephalic extraction of a live female newborn weighing 2,950 g with an Apgar score of 10/10 at the 1, 5 and 10 minutes of life and the reconstructive surgery for various malformations. The post-operative period was simple and the patient was discharged on day 15. Conclusion: This rare case of multiple congenital malformations during pregnancy highlights the importance of prenatal follow-up, ultrasound assessment and multidisciplinary management.